Taiwanese Investment in Vietnam: Current Development and Issues - Nguyen, Hong Son (H. : ĐHQGHN, 2017)
Taiwan is the 4th largest foreign investor in Vietnam. Taiwanese FDI on the one hand has contributed to Vietnam’s economic development, on the other hand has raised some serious issues related to the country’s sustainable development. In order to analyze the current evelopmentnd emerging issues related to Taiwanese investment in Vietnam, this paper focused on the following contents: (i) Characteristics of Taiwanese FDI inflows in comparison with the FDI flows into Vietnam in general; (ii) Some issues arising during the operation of Taiwanese FDI enterprises in Vietnam and those arising in the context of Vietnam’s international economic integration and economic restructuring; (iii) Opportunities to attract high - quality FDI from Taiwan towards sustainable development and some policy implications for Vietnam. The results show that FDI flows from Taiwan have increased significantly, especially since Vietnam joined the WTO. Taiwanese outward FDI into Vietnam focused mostly on labor-intensive sectors such as manufacturing of metals, chemicals and textiles. Taiwanese FDI contributed 2.2-2.3% of Vietnam’s total social investment; created 1.2 million jobs and helped improve the industrial structure. However, Taiwanese FDI is also characterized by low and medium level technology; sharp increase in “dirty industries” classified by Mani and Wheeler (1997) and social problems related to local labor. In the context of Vietnam’s shift to encourage development of high value added manufacturing and services sectors and the country’s direction of sustainable development, IT, electronic products as well as education and training may be the most promising sectors for Taiwanese investment in Vietnam in the future.